Juridical Analysis of Investment in Batam : Case Study in The Rempang-Galang Area - Nurlaelah Nurlaelah; Darwis Anatami; Sayid Fadhil; Soerya Respationo; Erniyanti Erniyanti (Asosiasi Penelitian dan Pengajar Ilmu Sosial Indonesia, 2024)
Investment is an essential instrument for capitalist countries to boost the national economy and create job opportunities for the community. Investment in Indonesia began with Foreign Investment Law No. 56 of 1964, which was later updated with Foreign Investment Law No. 25 of 2007 in line with the times. To increase investor interest in entering Indonesia, the government enacted Job Creation Law No. 11 of 2020, which was further updated through the Job Creation Law up to 2023. Due to the complexity and increasing number of investors facing obstacles such as land acquisition and regional policies, a Presidential Regulation on National Strategic Projects (PSN) was issued. The government's hopes and expectations for smooth investor operations do not always align with implementation. Specifically, PSNs often result in agrarian conflicts for local residents whose land is taken over for PSN purposes. In the context of investment in Batam, particularly the Rempang Eco-City Development Plan in the Rempang-Galang area, clashes occurred and drew national attention and concern from various experts when land measurements began by PT MEG, escorted by the Joint Team comprising police, TNI, and the Ditpam Batam Management Agency (BP Batam). They have not reached an agreement but are already being pushed for swift execution. The obstacles to investment in the PSN Rempang Eco-City include conflicts arising from legal uncertainties over land ownership since the administrative change from Bintan Selatan District to Batam City, becoming Galang District since 1980. Represented by their legal counsel LBH GP Asnhor, they demand legal certainty over their ancestral land to be issued certificates, enabling fair and humane compensation. This demand has been submitted to President Joko Widodo regarding the request for land legality for the villages on Rempang Island, Galang Island, and New Galang Island on behalf of the chairman of the Local Indigenous People's Relatives (KERAMAT) Gerisman Ahmad. Due to these obstacles and conflicts, the central government, through President Joko Widodo, issued Presidential Regulation No. 78 of 2023 on Handling Social Community Impacts in the Context of Land Provision for National Development. However, as of July 2024, there has not been a comprehensive agreement between the community, the Batam City government, and the head of BP Batam. The government is taking a softer approach by personally approaching residents to relocate to Tanjung Banon, where four model houses have been provided as promised incentives for those willing to move.